Can AIDS Education change Sexual Behaviour? - Gboyego A. Ogunbanjo; R.J. Henbest (South African Family Practice)
Objective: To determine if AIDS education can change the sexual behaviour of high school students. Design: Randomized controlled trial. Setting: Kwaggafontein. A rural township in KwaNdebele. Mpumalanga Province, South Africa. Participants: 352 students from the three high schools in the township were allocated to study and control groups. The study group received an AIDS education package developed by the Medical Research Council of South Africa, while the control group received education on general hygiene. Main outcome measures: Awareness of AIDS, knowledge about AIDS and self-reported sexual behaviour before and after the study. Results: The study group showed a dramatic increase in awareness of AIDS as a problem in their community (44% to 74% P=0.00) and knowledge about AIDS as a preventable (48% to 88% P=0.00) and an incurable disease (41% to 87% P=0.00). The control group did not, that is, (49% to 43% P=0.49), (48% to 58% P= I.32) and (44% to 45% P=0.93) respectively. Most importantly, the study group showed a significant decrease in reported high-risk sexual behaviour following the AIDS education programme. Not only was there a significant increase in the reported use of condoms to prevent AIDS when sexual intercourse was anticipated (26% to 87% P=0.00), but there was a decrease in reported sexual intercourse with more than one partner (15% to 5% P=0.01) and a decrease in casual sex from 20% to l0% (P=0.03). The control group did not report significant changes in their sexual behaviour. Conclusion: An AIDS education programme such as the one tested in this study can significantly increase awareness and knowledge of AIDS and decrease high-risk sexual behaviour. The use of this package on a national scale is highly recommended.